Visual attention and emotional reactions to negative stimuli: The role of age and cognitive reappraisal. - Wirth, Maria; Isaacowitz, Derek M.; Kunzmann, Ute (Psychology & Aging, 2017)
Prominent life span theories of emotion propose that older adults attend less to negative emotional information and report less negative emotional reactions to the same information than younger adults do. Although parallel age differences in affective information processing and age differences in emotional reactivity have been proposed, they have rarely been investigated within the same study. In this eye-tracking study, we tested age differences in visual attention and emotional reactivity, using standardized emotionally negative stimuli. Additionally, we investigated age differences in the association between visual attention and emotional reactivity, and whether these are moderated by cognitive reappraisal. Older as compared with younger adults showed fixation patterns away from negative image content, while they reacted with greater negative emotions. The association between visual attention and emotional reactivity differed by age group and positive reappraisal. Younger adults felt better when they attended more to negative content rather than less, but this relationship only held for younger adults who did not attach a positive meaning to the negative situation. For older adults, overall, there was no significant association between visual attention and emotional reactivity. However, for older adults who did not use positive reappraisal, decreases in attention to negative information were associated with less negative emotions. The present findings point to a complex relationship between younger and older adults' visual attention and emotional reactions. (PsycINFO Database Record